Specialized metabolites present in Camellia reticulata nectar inhibit the growth of nectar‐inhabiting microorganisms - Xun, Lijie; Huang, Rong; Li, Qiongyan; Meng, Qingxin; Su, Rui; Wu, Xiaoman; Zhang, Renbin; Li, Linshu; Gong, Xueyang; Dong, Kun (Frontiers in Plant Science, 2025)
Plant specialized metabolites are species-specific compounds that help plants adapt and survive in constantly changing ecological environments. Nectar contains various specialized metabolites, essential for maintaining nectar homeostasis. In this study, we employed high-performance liquid chromatography (HPLC) to compare the sugar composition between spoilage nectar and natural nectar, with further analysis of variations in color, odor, pH, and hydrogen peroxide (H₂O₂) content. Microbial strains in Camellia reticulata nectar were isolated and identified using the spread plate method coupled with DNA sequencing. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was implemented to characterize metabolite differences between spoilage and natural nectars. Subsequent in vitro experiments were conducted to validate the effects of screened nectar metabolites on the isolated microbial strains. The results showed that some C. reticulata nectar could spoil and deteriorate, which disrupted nectar homeostasis and significantly reduced the pollination efficiency by pollinators. Spoilage nectar had significant differences in color, odor, sugar composition, pH, and H2O2 content compared to natural nectar. The number of microbial species and quantity in spoilage nectar were much higher. The H2O2 content in natural nectar could reach (55.5 ± 1.80) μM, while it was undetectable in spoilage nectar. A total of 15 distinct microbial strains and 364 differential metabolites were isolated and identified from two types of nectar. In vitro experiments demonstrated that H2O2 could inhibit all the bacteria in C. reticulata nectar except Serratia liquefaciens. 12-Methyltetradecanoic Acid inhibited Bacillus subtilis, Curtobacterium flaccumfaciens, and Rothia terrae, and Myristic Acid only inhibited Rothia terrae. The nectar metabolites screened in this study had no effect on the nectar specialist yeast Metschnikowia reukaufii. In conclusion, the findings of this study revealed that C. reticulata nectar regulates the growth of microorganisms through its metabolites to maintain nectar homeostasis and prevent spoilage. This study improves the understanding of the physiological mechanisms of C. reticulata in maintaining nectar homeostasis and provides theoretical support for controlling nectar diseases and sustaining the reproductive fitness of C. reticulata. Future research could focus on further exploring the complex interactions between different metabolites in C. reticulata nectar and a wider range of microorganisms. Moreover, the development of practical applications based on these findings, such as the development of natural preservatives for nectar-related products or the optimization of pollination efficiency in C. reticulata cultivation, could be an important area for future exploration.